KOMPARASI PAKET PEMUPUKAN DI TINGKAT PETANI DAN PUPUK ANJURAN TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalanicum. L) DI KECAMATAN TANJUNG-BREBES - Vidya Mar'atusholikha (FP AGRO 16 UMY 024, 2016)
A research about Comparison Fertilizing Package of Farmer level and agriculture instructor level to Growth and Production of Shallot at Sub Distric Tanjung, Regency Brebes has been done from Januari until March 2016. This research used survey method consist of observation, primary and secondary data collecting that analyzed using Descriptive, T-test, and Regression. The sample was taken by Stratified Random Sampling. The result indicated that the farmers were not influenced by agriculture instructor in the other way farmers were influenced by cost, knowledge, culture and the number of the farmer.